2000
DOI: 10.1046/j.1365-2443.2000.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation mechanisms of mouse clock transcription factors, mClock and mArnt3

Abstract: Background: The Arnt3 (also termed as BMAL1 or MOP3)/Clock heterodimer is a positive regulator of circadian rhythm and activates the transcription of target genes such as per1 and vasopressin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
90
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 33 publications
7
90
1
1
Order By: Relevance
“…2B). These results support a previous study in which the C-terminal region of BMAL1 was shown to be required for its transcriptional activation function (19). Importantly, similar to Flag-BMAL1-Bm29 (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2B). These results support a previous study in which the C-terminal region of BMAL1 was shown to be required for its transcriptional activation function (19). Importantly, similar to Flag-BMAL1-Bm29 (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Similar results were obtained when Flag-BMAL1(L554X) was replaced by Flag-BMAL1(E447X) or Flag-BMAL1(I584X) (data not shown). Taken together, these data indicate that the C-terminal 43 aa of BMAL1 protein contain a domain that is essential for mammalian circadian oscillator performance and that, consistent with recent reports that show interaction of p300͞CREB-binding protein coactivators by means of the C-terminal region of BMAL1 (19)(20)(21), this domain must be involved in transcription activation.…”
Section: Resultssupporting
confidence: 90%
“…This Cterminal end of mBMAL1 was previously implicated in transcriptional activation in both yeast and mammalian cell culture (22). The authors of that study suggested that the C terminus of mBMAL1 is the primary transactivation domain of mCLK: mBMAL1, and that the C terminus of mCLK may serve only to augment or stabilize the activity of mBMAL1 (22). The conservation of this BMAL C-terminal region ("BCTR") in apBMAL suggests that apBMAL may also possess a C-terminal transactivation domain.…”
Section: Resultsmentioning
confidence: 97%
“…Because the mutant mCLK protein (mCLK⌬19) is defective for transcriptional activation (21), this region may be an important part of the transactivation domain, even though it does not contain polyglutamine stretches. Alternatively, the "⌬19" region may be involved in stabilizing the CLK:BMAL heterodimer (22), or function as a binding site for important regulatory proteins, such as PER (see below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation